"It's always on the safe list": Investigating experiential accounts of picky eating adults. (1st November 2018) - Fox, Gemma; Coulthard, Helen; Williamson, Iain; Wallis, Debbie
Abstract: Previous research into severely restricted eating for reasons which are not cultural, medical, due to a lack of food or due to concerns about body image has focused predominantly on "picky/fussy eating" in children. Despite evidence that picky eating does continue into adulthood and recognition in the new diagnostic category Avoidant Restrictive Food Intake Disorder (ARFID) that problematically avoidant and restrictive patterns of eating affect people across the lifespan, relatively little is known about the challenges and consequences faced by older adolescents and adults. This research employs qualitative methods to explore the experience of living as an adult with picky eating behaviours. Semi-structured interviews were undertaken with thirteen adults who identify as picky eaters and eat a highly limited diet, as determined by a checklist food questionnaire. Data were analysed using interpretative phenomenological analysis (IPA). Two themes are presented in this paper: "Constructions of food" and "Motivators for and barriers to change". These themes show the importance of how individuals perceive food, their diet and themselves, and implications for clinical practice and future research in light of these findings are considered.